Effects of Osmotic, Thermal and Plant Growth Regulators Seed Priming on Different Wheat Varieties - Ahmed, MGU; Khatun, F; Islam, Z (Journal of Bio-Science, 2021)
Proper germination and proper growth of seedlings in conventional farming methods are often not achieved at the desired rate. The purpose of priming is to reduce germination time and improve stand and percentage of germination and increases vigour for fast and strong plant development. In order to evaluate the effect of seed priming on growth and yield of wheat the present study was conducted at Agronomy Farm House, Rajshahi University. Three wheat varieties (BARI Gom-24, BARI Gom-25 and BARI Gom-26) were tested with three groups of priming media (osmo-priming, thermos-priming and plant growth regulator priming) and control (non-soaked). Seeds were primed for 24 h at 25°C with four priming media, osmo-priming (1% NaCl, 2% KNO3, 2% KH2PO4, and 10% PEG), PEG-Priming (50 μM GA3 and 50 μM BAP) and thermo-priming (0°C, 5°C and 10°C) and control was without priming agent. All types of priming media were significantly different among their types for plant height (cm), tiller number and dry biomass (g). PEG was significantly different in osmo-priming, GA3 was significantly different in PGR-priming and 0°C was significantly different in thermo-priming. In case of vigor index, 2% KH2PO4 was suitable among osmo-priming, GA3 was better than BAP priming and 0°C was optimum among all temperature priming. Seed priming helps seeds to grow rapidly and evenly in the field, producing healthier and faster maturing crops with better yields. J. Bio-Sci. 29(2): 111-122, 2021 (December)